Workday Sitting Time and Marital Status: Novel Pretreatment Predictors of Weight Loss in Overweight and Obese Men - Philip J. Morgan PhD; Jenna L. Hollis PhD; Myles D. Young PhD; Clare E. Collins PhD; Pedro J. Teixeira PhD (American Journal of Men's Health, 2018)
The evidence base for weight loss programs in men is limited. Gaining a greater understanding of which personal characteristics and pretreatment behaviors predict weight loss and attrition in male-only studies would be useful to inform the development of future interventions for men. In December 2010, 159 overweight/obese men (mean age = 47.5 years; body mass index = 32.7 kg/m 2 ) from the Hunter Region of New South Wales, Australia, participated in a randomized controlled trial testing the effectiveness of two versions of a 3-month gender-targeted weight loss program. In the current analyses, social–cognitive, behavioral, and demographic pretreatment characteristics were examined to determine if they predicted weight loss and attrition in the participants over 6 months. Generalized linear mixed models (intention-to-treat) revealed weight change was associated with education level ( p = .02), marital status ( p = .03), fat mass ( p = .045), sitting time on nonwork ( p = .046), and workdays ( p = .03). Workday sitting time and marital status accounted for 6.5% ( p = .01) of the variance in the final model. Attrition was associated with level of education ( p = .01) and body fat percentage ( p = .01), accounting for 9.5% ( p = .002) of the variance in the final model. This study suggests men who spend a lot of time sitting at work, especially those who are not married, may require additional support to experience success in self-administered weight loss programs targeting males. Additional high-quality evidence is needed to improve the understanding which pretreatment behaviors and characteristics predict weight loss and attrition in men.